Evaluating the growth pattern and relative performance in Nipah virus research from 1999 to 2010 - S.A., Sanni; Safahieh, H.; A.N., Zainab; A., Abrizah; Raj, R.G.; Sanni, S.A.; Safahieh, H.; Zainab, A.N.; Abrizah, A.; Raj, R.G. (Malaysian Journal of Library and Information Science, 2017)
Sanni, S. A., Safahieh, H., Zainab, A. N., Abrizah, A., & Raj, R. G. (2013). Evaluating the growth pattern and relative performance in Nipah virus research from 1999 to 2010. Malaysian Journal of Library & Information Science, Vol.18, no. 2: 14-24. The study examines Nipah virus publications retrieved from SCI-Expanded and SSCI database (Web of Science) for the period 1999–2010. Performance indicators used are: total publications, total citations, the activity index, the attractive index and the publication efficiency index. Yearly publication and citation trends indicated an exponential growth. The most active countries involved are USA, Australia, Malaysia, France, Germany and the UK. The USA produced the most papers, has the highest average citations per article and highest h-index. Australia is the most productive country based on per capita followed by Malaysia. The relative citation impact in Nipah virus research by these countries surpassed the world’s average. The most active institutions are the Commonwealth Scientific and Industrial Research Organization, Australia (18.73%); Center for Disease Control and Prevention, USA (14.94%); and University of Malaya, Malaysia (12.41%).